Replication of association of IL1 gene complex members with ankylosing spondylitis in Taiwanese Chinese. - Chou, C; Timms, A; Wei, J; Tsai, W; Wordsworth, B; Brown, M (2006)
OBJECTIVE: To test the association of interleukin 1 (IL1) gene family members with ankylosing spondylitis (AS), previously reported in Europid subjects, in an ethnically remote population. METHODS: 200 Taiwanese Chinese AS patients and 200 ethnically matched healthy controls were genotyped for five single nucleotide polymorphisms (SNPs) and the IL1RN.VNTR, markers previously associated with AS. Allele, genotype, and haplotype frequencies were compared between cases and controls. RESULTS: Association of alleles and genotypes of the markers IL1F10.3, IL1RN.4, and IL1RN.VNTR was observed with AS (p<0.05). Haplotypes of pairs of these markers and of the markers IL1RN.6/1 and IL1RN.6/2 were also significantly associated with AS. The strongest associations observed were with the marker IL1RN.4, and with the two-marker haplotype IL1RN.4-IL1RN.VNTR (both p = 0.004). Strong linkage disequilibrium was observed between all marker pairs except those involving IL1B-511 (D' 0.4 to 0.9, p<0.01). CONCLUSIONS: The IL1 gene cluster is associated with AS in Taiwanese Chinese. This finding provides strong statistical support that the previously observed association of this gene cluster with AS is a true positive finding. These authors contributed equally to the study.